Association of HLA-B*5801 allele and allopurinol-induced stevens johnson syndrome and toxic epidermal necrolysis: a systematic review and meta-analysis - Lohitnavy Manupat; Saokaew Surasak; Eickman Elizabeth E; Somkrua Ratchadaporn; Chaiyakunapruk Nathorn (BMC, 2011)
Abstract Background Despite some studies suggesting a possible association between human leukocyte antigen, HLA-B*5801 and allopurinol induced Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN), the evidence of association and its magnitude remain inconclusive. This study aims to systematically review and meta-analyze the association between HLA-B*5801 allele and allopurinol-induced SJS/TEN. Methods A comprehensive search was performed in databases including MEDLINE, Pre-MEDLINE, Cochrane Library, EMBASE, International Pharmaceutical Abstracts (IPA), CINAHL, PsychInfo, the WHO International, Clinical Trial Registry, and ClinicalTrial.gov from their inceptions to June 2011. Only studies investigating association between HLA-B*5801 with allopurinol-induced SJS/TEN were included. All studies were extracted by two independent authors. The primary analysis was the carrier frequency of HLA-B*5801 comparison between allopurinol-induced SJS/TEN cases and each comparative group. The pooled odds ratios were calculated using a random effect model. Results A total of 4 studies with 55 SJS/TEN cases and 678 matched-controls (allopurinol-tolerant control) was identified, while 5 studies with 69 SJS/TEN cases and 3378 population-controls (general population) were found. SJS/TEN cases were found to be significantly associated with HLA-B*5801 allele in both groups of studies with matched-control (OR 96.60, 95%CI 24.49-381.00, p < 0.001) and population-control (OR 79.28, 95%CI 41.51-151.35, p < 0.001). Subgroup analysis for Asian and Non-Asian population yielded similar findings. Conclusion We found a strong and significant association between HLA-B*5801 and allopurinol-induced SJS/TEN. Therefore, HLA-B*5801 allele screening may be considered in patients who will be treated with allopurinol.